2014
DOI: 10.3897/zookeys.464.8155
|View full text |Cite
|
Sign up to set email alerts
|

A new species and synonymy of the Neotropical Eucelatoria Townsend and redescription of Myiodoriops Townsend

Abstract: The New World tropics represents the most diverse region for tachinid parasitoids (Diptera: Tachinidae), but it also contains the most narrowly defined, and possibly the most confusing, tachinid genera of any biogeographic region. This over-splitting of genera and taxonomic confusion has limited progress toward our understanding the family in this region and much work is needed to revise, redefine, and make sense of the profusion of finely split taxa. In a recent analysis of the Neotropical genus Erythromelana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Inclán and Stireman (2014) point out that the tropics of the New World are the most diverse region for tachinid parasitoids, but also have the most closely defined genera of tachinids as well as the most confusing ones of any biogeographic region. Thus, the species found in the present study were identified at the genus level.…”
Section: Discussionmentioning
confidence: 99%
“…Inclán and Stireman (2014) point out that the tropics of the New World are the most diverse region for tachinid parasitoids, but also have the most closely defined genera of tachinids as well as the most confusing ones of any biogeographic region. Thus, the species found in the present study were identified at the genus level.…”
Section: Discussionmentioning
confidence: 99%